Protecting data in cloud environment with attributebased encryption. (2015) - Zhu, Shuaishuai; Yang, Xiaoyuan
Traditional file systems cannot satisfy the recent requirements in the cloud environment. Meanwhile, current file systems designed for cloud computing cannot provide enough flexibility, finegrained access control and access security. In this paper, a novel secure file sharing scheme based on attribute control is presented. In order to design a practical cloud file system with attribute based encryption, we give a systematic definition of attribute computing in cloud computing environment. Based on the definition, we present a secure and practical attribute based encryption scheme without pairings (CPABEWP) under cloud computing scenarios. Then we design a secure cloud file system applying our CPABEWP to provide data management and secure data sharing. According to our analysis and test, the scheme is chosen plaintext secure in selective ID model with acceptable performance and can satisfy the file sharing application in cloud computing.